CABI Compendium 2022
DOI: 10.1079/cabicompendium.56926
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas hortorum pv. carotae (bacterial blight of carrot)

Abstract: This datasheet on Xanthomonas hortorum pv. carotae covers Identity, Overview, Distribution, Dispersal, Hosts/Species Affected, Diagnosis, Biology & Ecology, Environmental Requirements, Seedborne Aspects, Impacts, Uses, Prevention/Control, Further Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although yield losses may occur in carrot fields with high incidences of bacterial blight, the economic impact of the disease is considered to be minimal in general. However, the highest seriousness of this pathogen is presented in regard to the seed quality [ 9 ]. Regarding the host resistance, a germplasm screening of carrot species indicated that four PI lines and two of the wild relatives are highly resistant against Xhc [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although yield losses may occur in carrot fields with high incidences of bacterial blight, the economic impact of the disease is considered to be minimal in general. However, the highest seriousness of this pathogen is presented in regard to the seed quality [ 9 ]. Regarding the host resistance, a germplasm screening of carrot species indicated that four PI lines and two of the wild relatives are highly resistant against Xhc [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Xhc, the International Seed Testing Association (ISTA) recommends a seed wash dilution-plating assay including washing seeds in buffer and plating serial dilutions of the extract on a semi-selective medium. Either a pathogenicity test or a polymerase chain reaction (PCR) is used to confirm suspect isolates [ 9 , 11 ]. In 2019, the gel-based PCR assay [ 12 ] was replaced by a TaqMan assay consisting of two pairs of Xhc specific primers and probes targeting specific markers Xhc3S and Xhc02 [ 13 , 14 ] and one set of universal primers and probe detecting a part of the 16S rRNA gene [ 15 ].…”
Section: Introductionmentioning
confidence: 99%